(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the various methods of forecasting demographic processes, exploring their applications and the conditions under which they are most effective. It examines statistical, mathematical, and computational techniques used in demographic forecasting, including cohort-component models, time-series analysis, and machine learning algorithms.